Who contributes efficiently to development? evaluating agricultural R&D in Cameroon and Tanzania - Hartwich, Frank; von Oppen, Matthias (2006)
The article presents results from an evaluation of the technical efficiency of agricultural research and development (R&D) activities at universities and government research organizations in Cameroon and Tanzania. Data Envelopment Analysis (DEA) is used to measure multiple-input multiple-output relations in the R&D process. The calculations are expanded with qualitative information about the relevance of R&D to its users applying the Analytic Hierarchy Process (AHP) method in which peers rate the relevance of R&D outputs. The findings suggest that though the evaluated universities did not have a mandate for development-oriented R&D, they were as efficient in conducting agricultural R&D as national agricultural research organizations or international agricultural research centers. International research centers were found to generate relevant R&D outputs, but at high costs, particularly with regard to the international staff they use. The new process evaluation method tested in the study allows to compare the efficiency with which research entities operate in order to make better micro management decisions, e.g., whom to involve and whom to encourage to become more efficient. The method is complementary to economic impact assessment of agricultural R&D which is usually conducted at the more aggricated program level.